Islamic Philanthropy and Sharia Compliance: Family Empowerment at Yayasan Baitul Māl (YBM BRILiaN) Yogyakarta, Indonesia - Ahmad Syawal; Sedya Santosa; Musdalifa (Al-Amwal : Journal of Islamic Economic Law, 2026)
Purpose-This study aims to: (1) analyze how YBM BRILiaN RO Yogyakarta designs and implements its Family Strengthening Program as a model of Islamic philanthropic intervention; (2) evaluate its compliance with fiqh muamalah principles and Indonesian zakat law (Law No. 23 of 2011); and (3) identify the institutional challenges in its execution. Method-This study employs a qualitative case study design with a retrospective institutional perspective. To methodology integrates: (1) a legislative approach analysing Law No. 23/2011, Government Regulation No. 14/2014, and DSN-MUI fatwas on productive zakat; and (2) a conceptual normative-juridical approach employing maqashid al-shariah and fiqh muamalah to evaluate program compliance. Data were collected via structured interview with the program supervisor and the institution's official documentation video, analyzed through thematic categorization combined with normative-juridical analysis. Result-The Islamic philanthropy program operates on a three-year cycle: spiritual, educational, and health coaching (Year 1); economic empowerment via MIGP (Year 2); and independence with social contributions (Year 3), achieving the mustahik-to-muzakki transformation evidenced by voluntary infak, sedekah, and zakat contributions among Year 3 beneficiaries Key institutional challenges identified include beneficiary impatience during Year 1 and transactional participation patterns that require structural and motivational responses. Normative-juridical analysis further confirms: the MIGP capital constitutes hibah (unconditional grant) as the akad that operationalises the tamlik principle, compliant with Article 27 of Law No. 23/2011; recipients are correctly classified as asnaf al-fuqarā' and al-masākīn per QS. Al-Taubah: 60; and the three-year cycle holistically realises all five maqashid al-shariah objectives at the household level. Implication-This study provides theoretical and juridical contributions to Islamic philanthropy literature, offering a legally validated and replicable model for sharia-compliant family empowerment in Indonesia. Practical implications recommend stronger sharia governance mechanisms: formal written hibah documentation, consistent asnaf verification, and transparent fund disbursement.